Enhanced mesophilic bio-hydrogen production by co-digestion of raw rice straw and activated sewage sludge - Alemahdi, Nika (2015)
Huge amount of activated sewage sludge is being produced every year all over the world in wastewater treatment plants that if treated properly, has the potential to be used as inoculum and/or co-substrate for bio-hydrogen production. Activated sewage sludge and lignocellulosic waste material e.g rice straw have the potential to be used as a source for bio-hydrogen production. Pretreatment of lignocellulosic waste materials is often suggested by researchers to break the complex structure of these materials prior to dark fermentation. Pretreatment methods are costly, complicated and not environment-friendly due to high usage of acids, bases and energy. Therefore in this study try to find a way for bio-hydrogen production using raw materials. Batch bio-hydrogen production is carried out in serum bottles (150 mL) with maximum operation level of 120 mL and 30 mL headspace at mesophilic conditions (35°C). Activated sewage sludge (ASS) collected from inflow of a digestion tank in a wastewater treatment plant was used as the inoculum and co-substrate. Rice straw (RS) was used as the substrate. In order to achieve the highest bio-hydrogen yield and methanogens activity inhibition, heat treatment of inoculum was optimized at different exposure time and temperature ranges prior to the dark fermentation process. Three levels of time were defined (30, 45 & 60 min) and three levels of temperature (80, 90 and 100 °C) were chosen to conduct the experiments. Collected data was analysed using response surface methodology (RSM) as an analytical method. From the results, it was observed that the heat treatment of inoculum at 100 °C for 60 minutes produced the highest bio-hydrogen yield of 14.22 NmL H2/g VS at concentration of 70.97 % in total produced biogas. The triplicate batch tests were conducted to verify the optimum condition introduced by RSM (100 °C for 60 minutes), resulted in 14.10 + 0.2 NmL H2/g VS at concentration of 69.45% in biogas. Production of 0.073 NmL CH4/gVS at 0.17% concentration of total biogas in these tests indicated a very successful achievement in inhibition of methanogens activity. The raw rice straw was also co-digested with heattreated inoculum (100 °C for 60 minutes) for bio-hydrogen production at different operating process parameters. Three levels of volatile solids (VS) ratio (2:1, 4:1 and 6:1) and three levels of initial pH (4, 4.75 and 5.5) were defined as numerical variables. 4 categories of substrate size were tested to achieve the objective aforesaid: “Intact RS” [20-30 mm], “Intact RS ,Fine RS [0.25-0.5mm],Medium RS (0.5-2mm] and Large RS (2-20mm). Using RSM, the highest bio-hydrogen yield of 14.70 NmL /g VS was recognized at the optimum initial pH of 5.01 and VS ratio of 4.54 : 1 from the “Large RS” particles. Triplicate batch tests were done to produce bio-hydrogen applying optimized factors; these tests have average bio-hydrogen yield of 14.54 + 0.29 NmL /g VS. By finding optimum VS ratio, pH and proper size of rice straw, we are able to achieve higher yield of bio-hydrogen production compared to other works in mesophilic conditions using mixed culture as inoculum and lignocellulosic waste materials as substrate. The overall results in this study indicated that codigestion of raw rice straw as substrate and activated sewage sludge as both co-substrate and inoculum is a feasible approach for bio-hydrogen production.